The Frontier Gandhi, his place in history - Korejo, M. S. (Muhammad Soaleh), 1923- (Karachi : Oxford University Press, 1993)
On the life of Abdul Ghaffar Khan, 1891-1988, prominent Pushtun political leader.
Includes bibliographical references and index.
Keywords: Khan, Abdul Ghaffar, -- 1890-1988.; Pakistan -- Politics and government